Exploring the relationship between IGHMBP2 gene mutations and spinal muscular atrophy with respiratory distress type 1 and Charcot-Marie-Tooth disease type 2S: a systematic review - Tian, Yuan; Xing, Jinfang; Shi, Ying; Yuan, Enwu (Frontiers in Neuroscience, 2023)
Background:IGHMBP2 is a crucial gene for the development and maintenance of the nervous system, especially in the survival of motor neurons. Mutations in this gene have been associated with spinal muscular atrophy with respiratory distress type 1 (SMARD1) and Charcot-Marie-Tooth disease type 2S (CMT2S). Methods:We conducted a systematic literature search using the PubMed database to identify studies published up to April 1st, 2023, that investigated the association between IGHMBP2 mutations and SMARD1 or CMT2S. We compared the nontruncating mutations and truncating mutations of the IGHMBP2 gene and selected highfrequency mutations of the IGHMBP2 gene. Results: We identified 52 articles that investigated the association between IGHMBP2 mutations and SMARD1/CMT2S. We found 6 hotspot mutations of the IGHMBP2 gene. The truncating mutations in trans were all associated with SMARD1.This study provides evidence that the complete LOF mechanism of the IGHMBP2 gene defect may be an important cause of SMARD1.